APPLICATION DEVELOPMENT DURING 2020 COVID19 PANDEMIC - A CASE STUDY OF REKA - Maclean Patrick Sibat, -; Mohd Razif Baital @ Latif, -; Mahani Huja Husin, -
– Extra ordinary situations require extraordinary solutions and approaches in order to maintain the same level of productivity and efficiency in any given application development process. This is clearly true in order to circumvent the impact of the greatest disruptor to application development in the IT industry for 2020 – the COVID19 pandemic. In this case study paper, we look at the impact of REKA – a rapid development tool; developed in-house in Universiti Malaysia Sarawak (UNIMAS), towards the existing application development structure, practices and norms; and the ways it has helped maintain, if not exceed, the productivity levels of UNIMAS application developers during an adverse situation brought about by the COVID19 pandemic compared to productivity levels during past years. We look at the reasons REKA has been successful in meeting the application development needs of the university and the disruption it has caused towards existing established and accepted development methodologies employed by the application development teams at the Centre for IT Development & Services (CITDS), UNIMAS